Evaluation of CHB MLI based shunt APF using low pass filter and self-tuning filter - Musa Yusup Lada; Mohd Amran Mohd Radzi; Jasronita Jasni; Hashim Hizam; Auzani Jidin; Syahrul Hisham Mohamad (Institute of Advanced Engineering and Science, 2023)
The increasing demand for high-rating power supply in the distribution system causes the conventional inverter topology, six step voltage source inverter (SSVSI) unsuitable for being applied as active power filter (APF). Multilevel inverter (MLI) is generally the best suitable inverter for APF, but not all types of MLI can be used for high-voltage applications. Among the MLIs topology, cascaded H-bridge (CHB) is the best choice since it can produce output voltage more than twice the amount of DC source. Moreover, CHB MLI topology uses fewer power devices and is simple in design. Low pass filter (LPF) is a common method used for harmonic extraction in this controller. However, this method faces various problems, such as an additional need for phase lock loop (PLL) algorithm and slow transient and steady-state responses. Therefore, self-tuning filter (STF) is introduced as a new filtering method to overcome this problem. This paper evaluates CHB MLI's performance for APF using STF as a harmonic extraction. The model was developed and verified in MATLAB/Simulink. The results show that harmonic extraction using STF performs better total harmonic distortion (THD) than conventional LPF. Nevertheless, both algorithms produce THD below 5%, defined as the permissible value stated in IEEE 519.